Treatment‐emergent hypertension and efficacy in the phase 3 Study of (E7080) lenvatinib in differentiated cancer of the thyroid (SELECT). Issue 11 (14th April 2018) - Wirth, Lori J.; Tahara, Makoto; Robinson, Bruce; Francis, Sanjeev; Brose, Marcia S.; Habra, Mouhammed Amir; Newbold, Kate; Kiyota, Naomi; Dutcus, Corina E.; Mathias, Elton; Guo, Matthew; Sherman, Steven I.; et al.
Abstract : BACKGROUND: Hypertension (HTN) is an established class effect of vascular endothelial growth factor receptor (VEGFR) inhibition. In the phase 3 Study of (E7080) Lenvatinib in Differentiated Cancer of the Thyroid (SELECT) trial, HTN was the most frequent adverse event of lenvatinib, an inhibitor of VEGFR1, VEGFR2, VEGFR3, fibroblast growth factor receptor 1 (FGFR1), FGFR2, FGFR3, FGFR4, platelet‐derived growth factor receptor α (PDGFRα), ret proto‐oncogene (RET), and stem cell factor receptor (KIT). This exploratory analysis examined treatment‐emergent hypertension (TE‐HTN) and its relation with lenvatinib efficacy and safety in SELECT. METHODS: In the multicenter, double‐blind SELECT trial, 392 patients with progressive radioiodine‐refractory differentiated thyroid cancer (RR‐DTC) were randomized 2:1 to lenvatinib (24 mg/d on a 28‐day cycle) or placebo. Survival endpoints were assessed with Kaplan‐Meier estimates and log‐rank tests. The influence of TE‐HTN on progression‐free survival (PFS) and overall survival (OS) was analyzed with univariate and multivariate Cox proportional hazards models. RESULTS: Overall, 73% of lenvatinib‐treated patients and 15% of placebo‐treated patients experienced TE‐HTN. The median PFS for lenvatinib‐treated patients with (n = 190) and without TE‐HTN (n = 71) was 18.8 and 12.9 months, respectively (hazard ratio [HR], 0.59; 95% confidence interval [CI], 0.39‐0.88; P = .0085). For lenvatinib‐treated patients, the objective response rate was 69% with TE‐HTN and 56% without TE‐HTN (odds ratio, 1.72; 95% CI, 0.98‐3.01). The median change in tumor size for patients with and without TE‐HTN was −45% and −40%, respectively ( P = .2). The median OS was not reached for patients with TE‐HTN; for those without TE‐HTN, it was 21.7 months (HR, 0.43; 95% CI, 0.27‐0.69; P = .0003). CONCLUSIONS: Although HTN is a clinically significant adverse event that warrants monitoring and management, TE‐HTN was significantly correlated with improved outcomes in patients with RR‐DTC, indicating that HTN may be predictive for lenvatinib efficacy in this population. Cancer 2018;124:2365‐72 . © 2018 American Cancer Society . Abstract : In patients from the Study of (E7080) Lenvatinib in Differentiated Cancer of the Thyroid (SELECT) trial, treatment‐emergent hypertension has been correlated with improved progression‐free survival, objective response rates, and overall survival. Therefore, treatment‐emergent hypertension may be considered a predictive factor for the efficacy of lenvatinib.